Analysis of Factors Contributing to Readmission in Congestive Heart Failure Patients at Kota Kendari Hospital - Oza Jumatan Aso; Amiruddin Eso; Jamaluddin (Journal of Innovative and Creativity, 2025)
Patients with heart failure exhibit a significant risk of readmission. This study seeks to examine the influences of age, comorbidities, and medication adherence as determinants of readmission in patients with congestive heart failure at Kota Kendari Hospital. This research employed an observational analytic methodology with a case-control design. The case sample comprises congestive heart failure patients who experience readmission, whereas the control group consists of those who do not. The study sample comprised 43 case samples and 43 control samples. The data were evaluated utilizing the chi-square test, deemed significant if the p-value was less than 0.05, alongside the odds ratio test to assess the value of risk factors. Bivariate analysis results revealed that the characteristics associated with readmission risk in congestive heart failure patients included age (p = 0.009, OR = 3.168), comorbidities (p = 0.004, OR = 3.675), and medication adherence (p = 0.000, OR = 7.719). There is a correlation between congestive heart failure readmissions and age, comorbidities, and medication adherence.